The Letter of the Law: Literature, Justice and the Other - Dokou, Christina; Dokou, Christina; Mitsi, Efterpi; Dimakopoulou, Stamatina (Peter Lang, 2013)
This book combines legal as well as political and theoretical questions in a variety of contexts, ranging from legal issues in the early modern period to critical explorations of law/s, justice and textuality in contemporary literature and culture. The essays in this volume offer critical perspectives on the role of literature and theory in relation to the law and explore otherness and justice in early modern, Victorian and contemporary texts, postmodern theory, colonial and postcolonial contexts and popular culture. Examining how legal and literary narratives construct, repress, legitimise, but also enable the Other, this volume offers new insights into forms of alterity, marginality and exclusion and articulates the imperative need to reconfigure issues of justice as always intertwined with the Other.